2017
DOI: 10.1515/pjst-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Circadian Rhythm on Balance Performance

Abstract: Introduction. The aim of the study was to examine the effect of circadian rhythm on dynamic balance performance and to determine the role of physical activity level, body temperature, chronotype, and gender in this possible effect. Material andmethods. Forty-two young male and female subjects with different physical activity levels participated in the study. A dynamic equilibrium test, a Star Excursion Balance Test (SEBT), was conducted at 9:00, 13:00, and 17:00 on three different days with at least two days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Besides, the best scores of balance were found at 13:00 h and 17:00 h in a male group and in a trained group [5].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Besides, the best scores of balance were found at 13:00 h and 17:00 h in a male group and in a trained group [5].…”
Section: Introductionmentioning
confidence: 85%
“…The chronotype of the participants was not assessed before the first testing session. Although Karagul et al [5] found that chronotype did not affect the balance results of subjects with different physical activity levels, it must be considered in future studies. Finally, it is important to note that the concentric and eccentric hamstring torque was measured without consideration of other isokinetic parameters, like isometric torque, power, work, and fatigue.…”
Section: Limitationsmentioning
confidence: 92%
“…The evaluation process was planned between 12.00 and 16.00, as we wanted to avoid variations in performance values for the balance tests, especially their decrease if the tests were performed early in the morning or late in the evening [49][50][51]; as there are sources of fluctuations in performance for elite athletes generated by the circadian rhythm [52]. The investigation teams were reduced in number (6-8 people) in order to ensure a calm climate and to avoid disturbing factors with negative effects on performance due to the decrease in the ability to focus [53].…”
Section: Methodsmentioning
confidence: 99%
“…日常生活や運動において,姿勢や動作の安定性(身体 バランス)がよいことは転倒や怪我を防いだり,正確に 効率よく動いたりするなどのために重要である 1,2) .身体 バランスは,安静姿勢を保持するための静的バランスと, 重心を随意的に移動して動作目的を達成させようとする 動的バランスに分けられる 3) . 通常,多くの生理機能に日内変動が認められ,体温, 心拍数や覚醒度はいずれも早朝に低く,夕方に高い傾向 があることが示されている [4][5][6] .身体バランス機能の日 内変動についても調べられているが,その所見は必ずし も一致していない [6][7][8][9][10][11][12][13][14][15] .夜間睡眠をとらせた条件におい て,健常若年者(スポーツ愛好者を含む)を対象として, 午前と午後に静止立位での重心動揺検査を開眼と閉眼で 行った結果では 7,12) ,いずれにおいても身体の重心に近 似して動く足圧中心(COP)の動揺面積が午後の方が小 さかったことが認められている.この結果は動揺面積が より小さいことはバランス能力がより高いと評価される ため 1,16) 13) の 結果は,朝に比べて午後の時間帯の方が高かったことを 示している.これらの先行研究では身体バランス能力の 日内変動に対して主には体温 7,12,13,15) や覚醒度(眠気) 7,15) の影響が考えられている.一方で,静止立位での重心動 揺検査を開眼で行った結果や Cross Test に類似の身体バ ランス検査を行った結果から,静的および動的バランス 能力は朝の 9 時に高く,17 時,13 時の順に低くなった と報告している先行研究もある 14) .この先行研究では, その結果について成人男女(20-60 歳)を対象とした先 行研究 17) の所見などをもとに認知機能が朝に高くなっ ており,その影響を受けた可能性を推測している.これ ら以外にも,健常若年者を対象として重心動揺検査や SEBT を行った結果から,静的バランス能力と動的バラ ンス能力の両方について,朝に高く午後に低いという報 告 [9][10][11] や時刻の影響は認められない 6,8)…”
Section: 緒 言unclassified